Boston Consulting Group Sebagai Dasar Strategi pada PG Candi Baru Sidoarjo - Dwi Syahfitri; Eko Nurhadi; Indra Tjahaja Amir (Fakultas Pertanian, Universitas Timor, 2021)
PG Candi Baru Sidoarjo is experiencing increasingly competitive demands from home and abroad to enter the global market in the sugar industry. The existence of such competitive conditions will certainly have implications so it is necessary to know in advance the position of market growth in order to formulate the right strategy for the company. The research method is descriptive quantitative with calculations from the Boston Consulting Group. The results show that the position of the PG Candi Baru Sidoarjo market growth matrix is in the question mark quadrant position with the type of business that has a low market share, but has high market growth prospects with an acquisition value of 0.094 <1.